Profit Planning in Corporate Budgeting - Ika Sari Wahyudi (PT. BERBAGI TEKNOLOGI SEMESTA, 2023)
This study seeks to investigate corruption in Indonesia, a country where corruption is regarded as one of the immoral practices within organizations. Upon reviewing the existing body of study literature, it has been shown that a contributing factor to unethical behavior among managers is the influence imposed by organizations to attain success in meeting targets and budgets. This study examines the correlation between individuals' budgeting practices and their profit planning strategies. Negative human behaviors can potentially lead managers to engage in unethical conduct to attain high performance and meet ambitious targets. One potential approach entails granting management the flexibility to reassess the budget during the current fiscal year, alleviating the workload imposed by the company and mitigating unethical behaviors.